Pengaruh Kualitas Informasi Instagram terhadap Kepuasan Pengguna dalam Komunikasi Publik Digital PT Trans Marga Jateng - Yashfanya Putri Juniesta Auliani; Nadia Itona Siregar (Hulondalo Jurnal Ilmu Pemerintahan dan Ilmu Komunikasi, 2026)
The use of Instagram as a digital public communication medium has become increasingly important for infrastructure companies in delivering information to the public in a fast, timely, and interactive manner. However, studies on user satisfaction with social media in the toll road infrastructure sector remain limited compared to commercial, educational, and community sectors. This study aims to examine the effect of information quality on user satisfaction with the Instagram account @jasamarga_semarangsolo. The research employed an explanatory quantitative approach using a survey method. The population consisted of all followers of the @jasamarga_semarangsolo Instagram account, while the sample included 98 respondents selected through purposive sampling. Data were analyzed using simple linear regression. The results indicate that information quality has a positive and significant effect on user satisfaction with the Instagram account @jasamarga_semarangsolo. Information quality also explains 54.9% of the variation in user satisfaction. These findings suggest that accurate, relevant, complete, and timely information plays an important role in fulfilling users’ information needs and enhancing their satisfaction with the platform. The results support the Uses and Gratifications perspective, which explains that user satisfaction is formed when media successfully fulfills the information needs that motivate media use.